Sociological Juridical Review Regarding The Protection of Children's Rights as Witnesses in Criminal Acts of Abuse Committed by Children at the Investigation Stage - Nur Rokhman, Afif; Anoraga, Surya; Setiamandani, Emei Dwinanarhati (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2024)
Abstract Background: Witnesses are a form of evidence that is valid according to law because it is used to reveal a fact. The witness's statement can be extracted by the investigator, namely at the investigation stage. If the witness is a child, their rights are protected as regulated in Law No. 23 of 2006 concerning Child Protection. Purpose: This research aims to find out how children's rights are protected, the obstacles to providing protection, and efforts to overcome barriers to delivering protection rights for children as witnesses due to the crime of sexual abuse committed by children at the investigation stage in the jurisdiction of the Kepanjen Resort Police. Methods: This research uses a sociological juridical approach, data collection techniques in the form of interviews with investigators, and direct observation at the PPA Unit of the Kepanjen Police and Children who have been witnesses as a place for collecting primary data to carry out document studies in the form of official documents, reports and regulations used. Findings: The results reveal substantial inconsistencies in the age of criminal responsibility, limited compliance with the UN Convention on the Rights of the Child, and inadequate consideration of psychological maturity in determining culpability. Theoretical and Practical Implications: Research results show that in investigations of child abuse cases, children as witnesses have received guaranteed rights under the law . Originality/Novelty: The obstacles faced are classified as internal and external obstacles. So that in the future, PPA will tighten supervision and establish better cooperation with the government .